Peripheral blood GATA2 expression impacts RNF213 mutation penetrance and clinical severity in moyamoya disease - Ituro Inoue; Susumu Miyamoto; Kouji H Harada; Akio Koizumi; Yohei Mineharu; Yoshiki Arakawa; Takahiko Kamata; Mei Tomoto; Noriaki Sato; Yoshinori Tamada; Takeshi Funaki; Yuki Oichi; et al. (Stroke and Vascular Neurology)
Background The p.R4810K founder mutation in the RNF213 gene confers susceptibility to moyamoya disease (MMD) and non-MMD intracranial artery disease. However, penetrance is incomplete, and the underlying molecular mechanism remains unknown.Methods and results Transcriptome analysis of peripheral blood was conducted with nine MMD patients and five unaffected mutation carriers from four familial MMD pedigrees. Bayesian network analysis identified upregulated gene modules associated with lipid metabolism and leucocyte development (including GATA2 and SLC45A3), and epidermal growth factor receptor (EGFR) signalling (UBTD1). It also identified downregulated gene modules related to mitochondrial ribosomal proteins (RPS3A and RPL26), and cytotoxic T cell immunity (GZMA and TRGC1). The GATA2 network was replicated through weighted gene co-expression network analysis and further examined in a case–control study, comprising 43 MMD patients, 16 non-MMD patients, 19 unaffected carriers and 35 healthy controls. GATA2 exhibited a significant linear correlation with SLC45A3 and was significantly higher in MMD patients compared with age-matched and sex-matched unaffected carriers or wild-type controls. Among patients with the p.R4810K mutation, higher GATA2 expression was associated with an earlier age of onset, bilateral involvement and symptomatic disease onset.Conclusions Peripheral blood GATA2 expression was associated with increased penetrance of the RNF213 mutation and more severe clinical manifestations in MMD.